Evolution of intermetallics in a 26Cr–4Mo–2Ni (Ti + Nb) super ferritic stainless steel aged at 800°C. (April 2015) - He, M. L.; Yu, L. M.; Li, H. J.
<x content-type="archive" xml:space="preserve">Abstract</x> The precipitation of intermetallics in a 26Cr–4Mo–2Ni (Ti + Nb) super ferritic stainless steel during aging at 800°C was investigated. Optical, scanning electron and transmission electron microscopes and X-ray diffractometer were used to characterize the microstructure. Results show that the χ phase formed in 5 min and almost disappeared within 24 h. The σ phase began to form at grain boundaries when aged for 30 min and its amount increased with prolonged aging. After 24 h, the σ phase covered the grain boundaries and grew into the grain interiors. The Laves phase was found to form within 30 min.